Abstracting Dance: Detaching Ourselves from the Habitual Perception of the Moving Body - Aviv, Vered (Frontiers in Psychology, 2017)
This work explores to what extent the notion of abstraction in dance is valid and what it entails. Unlike abstraction in the fine arts that aims for a certain independence from representation of the external world through the use of non-figurative elements, dance is realized by a highly familiar object - the human body. In fact, we are all experts in recognizing the human body. For instance, we can mentally reconstruct its motion from minimal information (e.g., via a “dot display”), predict body trajectory during movement and identify emotional expressions of the body. Nonetheless, despite the presence of a human dancer on stage and our extreme familiarity with the human body, the process of abstraction is applicable also to dance. Abstract dance removes itself from familiar daily movements, violates the observer's predictions about future movements and detaches itself from narratives. In so doing, abstract dance exposes the observer to perceptions of unfamiliar situations, thus paving the way to new interpretations of human motion and hence to perceiving ourselves differently in both the physical and emotional domains.